2021
DOI: 10.3390/e23020211
|View full text |Cite
|
Sign up to set email alerts
|

Caputo Fractional Derivative and Quantum-Like Coherence

Abstract: We study two forms of anomalous diffusion, one equivalent to replacing the ordinary time derivative of the standard diffusion equation with the Caputo fractional derivative, and the other equivalent to replacing the time independent diffusion coefficient of the standard diffusion equation with a monotonic time dependence. We discuss the joint use of these prescriptions, with a phenomenological method and a theoretical projection method, leading to two apparently different diffusion equations. We prove that the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(18 citation statements)
references
References 51 publications
0
18
0
Order By: Relevance
“…Our analysis clearly shows the presence of crucial events, at least in the early stages of the germination process, and the presence of a transition to a stage where the scaling remains significantly anomalous, but the main origin of this anomaly is due to FBM which, according to Ref. [ 48 ], may be a sign of quantum coherence. The advocates of quantum mechanics to explain the origin of cognition may use these results to support their view.…”
Section: Discussionmentioning
confidence: 59%
See 3 more Smart Citations
“…Our analysis clearly shows the presence of crucial events, at least in the early stages of the germination process, and the presence of a transition to a stage where the scaling remains significantly anomalous, but the main origin of this anomaly is due to FBM which, according to Ref. [ 48 ], may be a sign of quantum coherence. The advocates of quantum mechanics to explain the origin of cognition may use these results to support their view.…”
Section: Discussionmentioning
confidence: 59%
“…The authors of Ref. [ 48 ] with the help of Ref. [ 43 ] demonstrated that the dynamical origin of FBM is a generalized Langevin equation that is derived using the formalism of quantum mechanics [ 49 ], thereby suggesting that FBM may be a manifestation of quantum coherence.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Mathematical models based on ordinal or partial differential equations have been successfully used to describe the behavior of systems through the space and time. On the other hand, although the origin is very old, it was not until recent years that fractional order differential equations have gained more attention in different areas of science; for example, they are very useful to describe complex systems with memory effects (see [1][2][3][4][5] and the references therein).…”
Section: Introductionmentioning
confidence: 99%